2009
DOI: 10.1037/a0014095
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the impact of membership turnover in small groups via latent class growth analysis: Modeling the rise of the New York Knicks of the 1960s and 1970s.

Abstract: In several areas of research, most notably in industrial/organizational psychology and in addictions treatment research, there have been calls for advances in modeling the impact of turnover in membership within dynamic small N groups. The present study examines the utility of latent class growth analysis (LGCA; in combination with other approaches) in modeling turnover in group membership within a dynamic work group from popular culture: the National Basketball Association's (NBA) New York Knickerbockers (Kni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Latent class growth analysis is a more statistically grounded alternative to manual classification and provides indices to assess model classification quality. 29 The analyses presented here were conducted from February 16, 2015, through February 20, 2015, using Mplus, version 7.11 (Muthén & Muthén), 30 with maximum likelihood estimation and the expectation maximization algorithm; ie, model parameters were estimated by maximizing likelihood functions across observations with and without missing values, assuming they were missing at random. 31 Dichotomous variables representing whether a man committed rape at each time point were used to indicate trajectory membership in the derivation and validation models.…”
Section: Discussionmentioning
confidence: 99%
“…Latent class growth analysis is a more statistically grounded alternative to manual classification and provides indices to assess model classification quality. 29 The analyses presented here were conducted from February 16, 2015, through February 20, 2015, using Mplus, version 7.11 (Muthén & Muthén), 30 with maximum likelihood estimation and the expectation maximization algorithm; ie, model parameters were estimated by maximizing likelihood functions across observations with and without missing values, assuming they were missing at random. 31 Dichotomous variables representing whether a man committed rape at each time point were used to indicate trajectory membership in the derivation and validation models.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, latent class membership accounts for individual differences (Muthén & Muthén, ); class differences can then be analyzed as a function of covariates to assess the level to which these variables are generally able to predict class membership. LCGA provides a more statistically grounded alternative to manual classification techniques and offers statistics related to model classification quality (Morgan‐Lopez, Cluff, & Fals‐Stewart, ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the NBA is a clear example of the kind of organizational environment with short horizons and time pressures where efficient membership transition is essential. NBA rosters undergo a large amount of turnover between and within seasons due to free agency and trades, with this player fluctuation often playing a significant role in a given team’s fortunes (Morgan-Lopez, Cluff, & Fals-Stewart, 2009). To be successful, teams need to bring in talented players who provide a good fit with current players and the organization as a whole.…”
Section: Methodsmentioning
confidence: 99%
“…Fortunately, findings from the NBA can generalize to other research contexts, as shown by previous research that has explored the parallels between professional sports and other organizational contexts (Keidel, 1984, 1987). Several studies have utilized the NBA specifically to examine a variety of organizational and group related topics relevant to the current study, including experience (Pfeffer & Davis-Blake, 1986), membership turnover (Morgan-Lopez et al, 2009), and knowledge translation (e.g., Berman, Down, & Hill, 2002). Therefore, it is reasonable to assume that the current study can provide more general insights for the effect of different experience types on individual performance embedded within larger group and organizational structures.…”
Section: Methodsmentioning
confidence: 99%